PERILAKU MAHASISWA DALAM MENENTUKAN PRODUK SYARIAH (Studi Pada Mahasiswa Ekonomi Syariah) - Luayyin, Reza Hilmy; Muhammad Nabat Ardli; Ahmad Syaifuddin Romli (LPPM STAI Muhammadiyah Probolinggo, 2024)
This study aims to analyze student behavior in determining sharia products using the Network Process (ANP) Analysis approach. The subject of the study was 73 Sharia Economics students who were respondents in this study. A qualitative descriptive approach is used to understand factors that affect student preferences, such as religiosity, knowledge, economic benefits, social environment, and constraints. Data were obtained through questionnaires that were analyzed using paired comparison matrices, normalization, and consistency calculations. The results of the study show that consumer behavior refers to the way individuals or groups make decisions to buy, use, and dispose of goods or services. It covers various aspects that influence purchasing decisions, such as: a). Decision Making Process b) Factors influencing c) Market Segmentation d) Trends and Changes. The results showed that religiosity had the highest priority weight (50.28%), followed by knowledge (26.02%), economic benefits (13.43%), social environment (6.78%), and constraints (3.48%). This shows that the aspect of religiosity is the main factor that affects students' preferences in choosing sharia products, while knowledge plays an important role in improving sharia financial literacy. The consistency of the data obtained was tested using the Consistency Ratio (CR), which yielded a value of 0.0835, indicating that the comparison data was consistent.